2015
DOI: 10.3310/hta19560
|View full text |Cite
|
Sign up to set email alerts
|

Psychological and psychosocial interventions for cannabis cessation in adults: a systematic review short report

Abstract: BackgroundCannabis is the most commonly used illicit drug worldwide. Cannabis dependence is a recognised psychiatric diagnosis, often diagnosed via theDiagnostic and Statistical Manual of Mental Disorderscriteria and theInternational Classification of Diseases, 10th Revision. Cannabis use is associated with an increased risk of medical and psychological problems. This systematic review evaluates the use of a wide variety of psychological and psychosocial interventions, such as motivational interviewing (MI), c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
36
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(37 citation statements)
references
References 79 publications
0
36
0
1
Order By: Relevance
“…Moreover, continued use of high potency cannabis appears to be more harmful to patients with psychosis than use of cannabis with lower THC and a relatively high proportion of CBD 46 . Sadly, clinical interventions to reduce cannabis use in patients with psychosis have been largely unsuccessful 47 . A recent study in patients with a first episode of psychosis found that patients experience both the positive and negative effect of cannabis more intensely compared to healthy controls 48 .…”
Section: Psychosismentioning
confidence: 99%
“…Moreover, continued use of high potency cannabis appears to be more harmful to patients with psychosis than use of cannabis with lower THC and a relatively high proportion of CBD 46 . Sadly, clinical interventions to reduce cannabis use in patients with psychosis have been largely unsuccessful 47 . A recent study in patients with a first episode of psychosis found that patients experience both the positive and negative effect of cannabis more intensely compared to healthy controls 48 .…”
Section: Psychosismentioning
confidence: 99%
“…Contingency Management (CM) is an evidence-based treatment for reducing marijuana use (Budney et al 2007; Cooper et al 2015; Davis et al 2015; Dennis et al 2004). Biochemical verification (e.g., urine toxicology) is typically an important aspect of abstinence-based CM.…”
Section: Introductionmentioning
confidence: 99%
“…However, data supporting this conclusion are mixed; 6-8 rather than opposite ends of the motivation spectrum, intrinsic and extrinsic motivation appear to exist more independently than earlier thought. 9-11 A recent review of treatments for cannabis dependence demonstrated that long-term follow-up results from interventions combining contingency management (i.e., giving vouchers for abstinence) and cognitive-behavioral therapy were better than for those using just one form of treatment, 12 suggesting that interventions targeting both intrinsic and extrinsic forms of motivation to change can be efficacious.…”
Section: How May a Behavioral Economic Approach Complement Other Treamentioning
confidence: 99%